2018
DOI: 10.12809/eaap181705
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Theta Asymmetry as a Biomarker of Depression

Abstract: Introduction: Electroencephalography (EEG) has been used extensively to study affective disorders. Quantitative spectral analysis of an EEG scan has been used to assess the biological basis of emotional disorders such as depression as well as to investigate biomarkers of affective disorders. Inter-hemispheric asymmetries in both baseline and stimulus-evoked frequencies (alpha, beta, theta, and delta) are potential biomarkers of depression. The role of frontal alpha asymmetry has been established, but other spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
(41 reference statements)
2
12
0
Order By: Relevance
“…The aim of distinguishing MDD and AN is to better understand EEG biomarkers and facilitate the early diagnosis and effective treatment of both these diseases ( 31 ). EEG frequencies (alpha, beta, theta, and delta) are potential biomarkers of depression ( 32 ). MDD and AN differ in theta oscillations (4–7 Hz) and the results show that there are differences in the eight electrodes of F3, O2, T3, P3, P4, FP1, FP2, and F8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of distinguishing MDD and AN is to better understand EEG biomarkers and facilitate the early diagnosis and effective treatment of both these diseases ( 31 ). EEG frequencies (alpha, beta, theta, and delta) are potential biomarkers of depression ( 32 ). MDD and AN differ in theta oscillations (4–7 Hz) and the results show that there are differences in the eight electrodes of F3, O2, T3, P3, P4, FP1, FP2, and F8.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that a higher baseline theta activity is associated with greater improvement in depression ( 46 , 47 ). Additionally, frontal theta asymmetry is also a potential biomarker of depression ( 17 , 32 ). In 2000, Suetsugi et al ( 9 ) suggested that frontal midline theta is a reliable measure of anxiety and that low levels of theta are associated with higher levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, psychosocial stress is one of the main sources of stress. It is Frontiers in Aging Neuroscience 09 frontiersin.org (Dharmadhikari et al, 2018). Cholinergic theta oscillation appears in human subjects with increased anxiety (Shin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The author proposes the frontal theta asymmetry model for estimating valence of evoked emotions and also suggested electrode reduction for neuromarketing applications [28, 29]. Author proposes frontal theta as biomarker of depression [30].…”
Section: Summary Of Reviewsmentioning
confidence: 99%
“…Author [21] studied the effect of the musical stimulus by recruiting musician and non-musician subject. Authors [30, 35] investigated the impact of the musical stimulus on mentally depressed subjects.…”
Section: Summary Of Reviewsmentioning
confidence: 99%